2023
DOI: 10.35848/1882-0786/acf7a9
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of time-dependent current and resistance of HTS closed loop with superconducting joint considering flux creep

Yasuaki Takeda,
Yuji Tsuchiya,
Gen Nishijima

Abstract: A low circuit resistance is required for a superconducting magnet operated in persistent mode using superconducting joints. We performed current decay measurements on a high-temperature superconducting (HTS) closed loop with a superconducting joint to evaluate the time dependence of the current and resistance. The results have been quantitatively explained by considering current sharing and flux creep. After the elapse of 105 s, current sharing was suppressed and a circuit resistance of less than 10−13 Ω was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…If superconducting joints must be used in regions (ii) or (iii), additional efforts must be made to achieve a lower R j . A recent study has shown that when I loop is close to I cj , R j is almost inversely proportional to the elapsed time and decreases with an increase in the pinning potential of a superconducting joint [49]. This may be effective for achieving a lower R j .…”
Section: Discussionmentioning
confidence: 99%
“…If superconducting joints must be used in regions (ii) or (iii), additional efforts must be made to achieve a lower R j . A recent study has shown that when I loop is close to I cj , R j is almost inversely proportional to the elapsed time and decreases with an increase in the pinning potential of a superconducting joint [49]. This may be effective for achieving a lower R j .…”
Section: Discussionmentioning
confidence: 99%